Vpliv značilnosti drevesnih vrst na prestrezanje padavin - Zabret, Katarina (Acta hydrotechnica, 2013)
Part of the gross precipitation that falls above the tree canopy does not reach the ground but is retained on the leaves and branches and on the ground vegetation in the forest. This process is known as rainfall interception and depends on different factors of which the most important are the meteorological factors and tree characteristics. Tree characteristics that influence interception and are often taken into account in research are tree crown size, canopy storage capacity, leaf area index and diameter at breast height, but sometimes also bark structure, tree height, leaf inclination and type of surface and hydrophobicity of leafs, branches and trunks. There are a lot of different methods for the determination of individual characteristics. Which method is used depends mainly on the available equipment, required measurement accuracy and study objectives. The influence of individual tree characteristics on interception is known, but rarely studied in detail due to the complexity of analysis for only one effect. Measurements of rainfall interception are very common and estimates of parameters are also performed due to the needs of different interception models.
Keywords: canopy storage capacity; indeks listne površine LAI; leaf area index LAI; prestrezanje padavin; rainfall interception; skladiščna zmogljivost krošnje; tree characteristics; značilnosti drevesnih vrst